2006
DOI: 10.3739/rikusui.67.69
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distributions of biomass and species composition in submerged macrophytes in the southern basin of Lake Biwa in summer of 2002

Abstract: Spatial distributions of the biomass and species composition in submerged macrophytes in the southern basin of Lake Biwa were surveyed in September, 2002. Macrophyte samples were collected from 52 sites by SCUBA. The total biomass (dry weight) of and the vegetated area of macrophytes in the southern basin during the study period were estimated as 10735 ± 3030 t, and 43 km 2 , respectively. Potamogeton maackianus was dominant, and Hydrilla verticillata, Ceratophyllum demersum, Egeria densa and Myriophyllum spic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The drastic changes in water quality associated with the decline in the water level caused a regime shift from phytoplanktondominated turbid water to macrophyte-dominated clear water (Hamabata and Kobayashi, 2002). This shift was particularly evident in the shallow, eutrophic south basin; the area of the south basin of Lake Biwa that was covered by submerged macrophytes was less than 6 km 2 between 1964 and 1994, but increased to 9 km 2 in 1995, 16 km 2 in 1997, 29 km 2 in 2000 and 43 km 2 in 2002 (Haga et al, 2006). Interestingly, the decline in the abundance of largemouth bass and the proliferation of bluegill in the south basin became obvious around 1995 (Nakai and Hamabata, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The drastic changes in water quality associated with the decline in the water level caused a regime shift from phytoplanktondominated turbid water to macrophyte-dominated clear water (Hamabata and Kobayashi, 2002). This shift was particularly evident in the shallow, eutrophic south basin; the area of the south basin of Lake Biwa that was covered by submerged macrophytes was less than 6 km 2 between 1964 and 1994, but increased to 9 km 2 in 1995, 16 km 2 in 1997, 29 km 2 in 2000 and 43 km 2 in 2002 (Haga et al, 2006). Interestingly, the decline in the abundance of largemouth bass and the proliferation of bluegill in the south basin became obvious around 1995 (Nakai and Hamabata, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The area occupied by submerged macrophytes increased almost fi vefold, from 6 km 2 in 1994 to 29 km 2 in 2000 (Hamabata and Kobayashi 2002), and it then reached 43 km 2 in 2002 (Haga et al 2006a). Haga et al (2006a) demonstrated that four native species, Potamogeton maackianus, Hydrilla verticillata, Ceratophyllum demersum, and Myriophyllum spicatum, and one exotic species, Egeria densa, accounted for 99% of the total biomass of submerged macrophytes.…”
Section: Introductionmentioning
confidence: 96%
“…Its surface area and mean depth are, respectively, 670 km 2 and 41 m (Shiga Prefecture 2005). The southern basin, which has a water surface area of 51.6 km 2 (Haga 2006) and a mean depth of 4 m (Shiga Prefecture 2005), has been rapidly occupied by submerged macrophytes during the past decade (Hamabata and Kobayashi 2002;Ohtsuka et al 2004;Haga et al 2006a). The area occupied by submerged macrophytes increased almost fi vefold, from 6 km 2 in 1994 to 29 km 2 in 2000 (Hamabata and Kobayashi 2002), and it then reached 43 km 2 in 2002 (Haga et al 2006a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of submerged macrophytes is influenced by many factors, such as nutrients, flow velocities, and bed sediments. Previous works report that the biomass of submerged macrophytes is correlated to bed-sediment nutrients and is affected by bedsediment texture, hydraulics (Asaeda et al 2004;Hung et al 2007;Haga et al 2006), and nutrients in the water, especially ammonium and phosphate (Feijoó et al 2002;Mony et al 2007). Other factors that influence the growth of submerged macrophytes are light conditions (Barko et al 1986;Maberly and Madsen 2002) and dissolved inorganic carbon (DIC) (Madsen and Maberly 1991;Rattray et al 1991;Madsen and Sand-Jensen 1994;Maberly and Madsen 2002;Vadstrup and Madsen 2006).…”
Section: Introductionmentioning
confidence: 99%